The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s10826-014-0009-2
|View full text |Cite
|
Sign up to set email alerts
|

Reunifying Families After an Out-of-Home Residential Stay: Evaluation of a Blended Intervention

Abstract: For youth placed in out-of-home residential care, there has been a trend towards shorter lengths of stay and earlier reentry into the community. In order to support reentry, we propose blending out-of-home residential care with aftercare services. In this study 89 youth that were in or at risk of entering the juvenile justice system received a unique blend of a behavioral-focused residential care program with a family based in-home aftercare service. Results indicate that youth displayed decreased behavior pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…A second factor is that treatment plans may focus on the presenting disruptive behaviors with limited attention on preparing the family and adolescent for discharge (Herbell & Breitenstein, 2020 ). Thus, families may feel unprepared for discharge, and adolescents may enter the same unchanged home environment (Ringle et al, 2015 ). Effective treatment plans should fully address the underlying trauma driving disruptive behaviors (Bryson et al, 2017 ).…”
Section: Parent Training and Treatment Gain Maintenancementioning
confidence: 99%
See 3 more Smart Citations
“…A second factor is that treatment plans may focus on the presenting disruptive behaviors with limited attention on preparing the family and adolescent for discharge (Herbell & Breitenstein, 2020 ). Thus, families may feel unprepared for discharge, and adolescents may enter the same unchanged home environment (Ringle et al, 2015 ). Effective treatment plans should fully address the underlying trauma driving disruptive behaviors (Bryson et al, 2017 ).…”
Section: Parent Training and Treatment Gain Maintenancementioning
confidence: 99%
“…A second parenting intervention that has been used with the RT population, Ringle & colleagues ( 2015 ) blended intervention, consists of RT combined with aftercare services for children at risk of entering the juvenile justice system. A key component of this model is an in-home family consultant working with families beginning at RT admission through three months post-discharge (Ringle et al, 2015 ).…”
Section: Prior Parent Training Programs In Rtmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, some researchers have not reported the coefficient α values obtained from their study-specific data, or have only reported α values from previous research as reference (e.g., Acri et al, 2017; Ringle et al, 2015). Both the omission and improper reporting of reliability estimates fall under a concept termed “reliability induction” (Henson & Thompson, 2002).…”
Section: Internal Consistency Reliability Of the Alabama Parenting Qu...mentioning
confidence: 99%